2020
DOI: 10.1007/s00125-020-05300-7
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of long-term vitamin D and n-3 fatty acid supplementation on inflammatory and cardiac biomarkers in patients with type 2 diabetes: secondary analyses from a randomised controlled trial

Abstract: Aims/hypothesis Interventions that reduce inflammation may delay progression of microvascular and macrovascular complications in diabetes. We examined the effects of vitamin D 3 and/or n-3 fatty acid supplementation vs placebo on 5 year changes in serum inflammatory and cardiac biomarkers in adults with type 2 diabetes. Methods This study reports pre-specified secondary outcomes of the Vitamin D and Omega-3 Trial to Prevent and Treat Diabetic Kidney Disease, in which 1312 US adults with type 2 diabetes and wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…IL10 increased in both groups. These results are similar to the reported effects of pro-inflammatory and anti-inflammatory cytokines to vitamin D supplementation and/or VDR activation in in vitro models and in human studies mostly including participants with conditions associated with increased inflammation [ 25–27 , 30 , 31 , 50 , 51 ]. It has been suggested that an increase in iron status after vitamin D supplementation is mediated through a decline in IL6 and TNFα and an increase in IL10 [ 8 , 21 , 29 , 52 , 53 ].…”
Section: Discussionsupporting
confidence: 89%
“…IL10 increased in both groups. These results are similar to the reported effects of pro-inflammatory and anti-inflammatory cytokines to vitamin D supplementation and/or VDR activation in in vitro models and in human studies mostly including participants with conditions associated with increased inflammation [ 25–27 , 30 , 31 , 50 , 51 ]. It has been suggested that an increase in iron status after vitamin D supplementation is mediated through a decline in IL6 and TNFα and an increase in IL10 [ 8 , 21 , 29 , 52 , 53 ].…”
Section: Discussionsupporting
confidence: 89%
“…Our findings of an inverse association between vitamin D status and fasting glycemia and the null association with HOMA-IR suggest an effect via insulin secretion rather than insulin resistance. Most RCTs have consistently shown a null association between vitamin D supplementation and cardiometabolic endpoints, including a recent trial examining intermediate endpoints (highsensitivity CRP and N-terminal pro-B-type natriuretic peptide) [8,9,[38][39][40][41]. However, some of these trials were of small sample size and short duration [40], used a low dose of vitamin D [41], were only powered to detect large effect sizes [8], and were not designed to study cardiometabolic diseases as primary endpoints [41].…”
Section: Discussionmentioning
confidence: 99%
“…In the OMEMI trial, the higher the EPA supplementation level was used in patients with recent acute myocardial infarction, the lower the risk of major cardiovascular events and the higher the risk of new atrial brillation (18). A secondary analysis of the STRENGTH test showed that Omega-3 fatty acid preparations had no effect on participants with high triglycerides and low HDL levels (19); The EPA and DHA interventions did not reduce the levels of in ammation or markers of heart failure in patients over ve years (20). In a population study, healthy subjects receiving EPA intervention increased the oxidative sensitivity of LDL, which may lead to atherosclerosis (21).…”
Section: Discussionmentioning
confidence: 99%